Revealing the potential of Netzwerk neu A1: A comparative study using Funk’s criteria and Mukundan et al.’s framework - Yuwono, Nurvi Alvi Laili Rohmatin; Wijayati, Primardiana Hermilia (Universitas Mulawarman, 2025)
This study aims to describe the alignment of Netzwerk Neu A1 with the criteria developed by Funk and Mukundan et al. as well as to examine the extent to which the textbook fulfills essential elements in German language teaching. This research employs a qualitative content analysis method. The data, consisting of the content in the Netzwerk Neu A1 textbook, were collected through documentation techniques and analyzed using Krippendorff’s content analysis model, which includes six main stages: (1) unitizing, (2) sampling, (3) recording or coding, (4) reducing, (5) inferring, and (6) narrating. The analysis process was carried out using an evaluation table based on the textbook criteria established by Funk and Mukundan et al. To ensure data validity, the analysis results were validated by expert reviewers. The findings indicate that Netzwerk Neu A1 meets all 14 criteria, which include aspects of media completeness, curriculum alignment, institutional compatibility, the four language skills, grammar, vocabulary, cultural content, evaluation, methodology, and physical appeal. Based on these findings, the textbook is considered appropriate and relevant for use in elementary-level German language instruction.